Increasing Customer's Saving Interest through Religiusity, Product Perception and Knowledge - Dahrul Siregar; Ahmad Harun Daulay; Saparuddin Siregar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The number of Islamic banks is not significant with the Muslim population in this country. The efforts to increase the number of customers and use of Islamic/ sharia products need to be increased. The aim of this study is to analyze the effect of religiosity, product perception and knowledge on people’s saving interest in Islamic banking products. The target population and sample in this study are 135 Moslems by using purposive random sampling technique. Data collection using a questionnaire. The results showed that all independent variables of religiosity, product perception and knowledge have a positive and significant effect on saving interest in Islamic banking products. The most dominant variable in influencing consumers' interest in saving is product perception.